Set of solutions using remote sensing and supervised learning to replace autoregressive integrated moving average models to forecast weather - CGIAR Research Program on Wheat (2020)
Meteorological indices can be used as substitutes for AIs. We discuss meteorological indexes and review SL approaches that are suitable for predicting drought based on historical satellite data.